Pretreatment with Bifidobacterium longum BAA2573 ameliorates dextran sulfate sodium (DSS)-induced colitis by modulating gut microbiota - Lin, Qiong; Hao, Wu-Juan; Zhou, Ren-Min; Huang, Cui-Lan; Wang, Xu-Yang; Liu, Yan-Shan; Li, Xiao-Zhong (Frontiers in Microbiology, 2023)
Objectives: Inflammatory bowel disease (IBD) is a chronic lifelong inflammatory disease. Probiotics like Bifidobacterium longum are considered to be beneficial to the recovery of intestinal inflammation by interaction with gut microenvironment. Our goals were to define the effect of exclusive use of BAA2573 on DSS-induced colitis, including improvement of symptoms, alleviation of histopathological damage, and modulation of gut microbiota. Methods: In the present study, we pretreated C57BL/6J mice with Bifidobacterium longum BAA2573, one of the main components in an over-the-counter (OTC) probiotic mixture BIFOTO capsule, before modeling with DSS.16S rDNA sequencing and liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based nontargeted metabolomic profiling were performed with collected feces. Results: We found that pretreatment of Bifidobacterium longum BAA2573 given by gavage significantly improved symptoms and histopathological damage in DSS-induced colitis mice. 57 genera and 39 metabolites were significantly altered after BAA2573 intervention. Pathway enrichment analysis demonstrated that Starch and sucrose metabolism, Vitamin B6 metabolism, and Sphingolipid metabolism may contribute to ameliorating colitis. Moreover, we revealed that the gut microbiome and metabolites were interrelated in BAA2573 intervention group, while Alistipes was the core genus. Conclusion: Our study demonstrates the impact of BAA2573 on the gut microenvironment and reveals a possible novel adjuvant therapy for IBD patients.